Case Report: Low Rectal Cancer With Incidental Pelvic Solitary Kidney - Zhang, Xiang; Chen, Chang; Wang, Kexin; Dai, Yong; Wang, Yanlei (Frontiers in Surgery, 2022)
Purpose Concurrence of pelvic solitary kidney and rectal cancer is a rare phenomenon. The presence of kidney in the narrow pelvic cavity represents a great challenge for total mesenteric excision (TME) under laparoscopy. Methods We reported a male patient with low rectal cancer and incidental pelvic solitary kidney, and reviewed relevant literatures. Results The patient was successfully treated with laparoscopic surgery and was discharged at day 6 postoperatively without severe complications. Conclusion This case suggests the feasibility of laparoscopic TME with pelvic solitary kidney in certain male rectal cancer patient, and emphasizes the importance of comprehensive preoperative radiological evaluation, multidiscipline team and careful intraoperative dissection.